1975
DOI: 10.1039/c39750000405
|View full text |Cite
|
Sign up to set email alerts
|

Stepwise Diels–Alder addition of hexafluorobut-2-yne to co-ordinated 1,3-dienes

Abstract: BS8 ITS)Summary Tricarbonyl(butadiene or 2,3-dimethylbutadiene)iron react with hexafluorobut-2-yne in a stepwise fashion yielding, as the final products, substituted tricarbonyl(cyc1ohexa-l,3-diene)iron complexes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

1975
1975
1997
1997

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The major photochemical event on ultraviolet irradiation of 380 , however, would not be the crucial η 4 to η 2 transition of the diene, but release of CO which does not lead to product. In refluxing hexane the carbon termini of the organic ligand in 381 are C−C connected and, under the reaction conditions, the resulting cyclohexa-1,4-diene in 382 immediately undergoes a 1,3-hydrogen shift to give the isolated cyclohexa-1,3-diene complex 383 . The authors suggest that the also photochemically induced [6+2] cycloaddition of (η 4 -cycloheptatriene)Fe(CO) 3 with dimethyl acetylenedicarboxylate (cf.…”
Section: Activation Of the Four-electron Component (Diene)mentioning
confidence: 99%
See 2 more Smart Citations
“…The major photochemical event on ultraviolet irradiation of 380 , however, would not be the crucial η 4 to η 2 transition of the diene, but release of CO which does not lead to product. In refluxing hexane the carbon termini of the organic ligand in 381 are C−C connected and, under the reaction conditions, the resulting cyclohexa-1,4-diene in 382 immediately undergoes a 1,3-hydrogen shift to give the isolated cyclohexa-1,3-diene complex 383 . The authors suggest that the also photochemically induced [6+2] cycloaddition of (η 4 -cycloheptatriene)Fe(CO) 3 with dimethyl acetylenedicarboxylate (cf.…”
Section: Activation Of the Four-electron Component (Diene)mentioning
confidence: 99%
“…The thermally allowed, concerted Diels-Alder addition reaction seems impossible for 1,3-butadienes that are η 4 -coordinated to metal fragments as in 380. Green et al, 606,607 however, have demonstrated the possibility of a stepwise reaction path (Scheme 54) from which compound 381 has been isolated in "moderate" yield. 607 The low yield of 381 can be explained by the fact that its formation implies the partial decoordination of the diene to form the intermediate in square brackets with η 2 -diene and coordinated alkyne.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…thermal cycloadditions (19). The exact manner in which this is achieved is not known but metals 0 might cause normally forbidden concerted reactions to proceed in a stepwise manner (20). The ability of metals to overconle large negative entropy factors by bindins both reactants in close proximity and in the proper orientation must also be important.…”
Section: T H F + Tlcpmentioning
confidence: 99%
“…Well-known examples include (i) cycloaddition of two 2π reactants that yield four-membered rings, (ii) 1,3-dipolar cycloaddition reactions that yield five-membered rings, , and (iii) Diels−Alder reactions that yield six-membered rings . Extensive efforts have recently been focused on the organometallic version of cycloaddition reactions, and these again can be subdivided into two major types: (i) the π systems of metal-bonded alkenes and polyenes participating in cycloaddition reactions ,, and (ii) cycloaddition to the free alkene or polyene within the metal π-complexes. , …”
mentioning
confidence: 99%